1501. Comparative Effectiveness of Antibiotic Therapy for the Outpatient Treatment of Urinary Tract Infections Among Otherwise Healthy, Premenopausal Women. (26th November 2018) - Butler, Anne M; Keller, Matthew R; Durkin, Michael J; Dharnidharka, Vikas R; Olsen, Margaret A
Abstract: Background: The comparative effectiveness of antibiotics for empiric therapy for urinary tract infection (UTI) is not well established. We sought to estimate the risk of treatment failure by guideline-recommended agent for treatment of UTI in otherwise healthy, premenopausal women. Methods: Using US commercial insurance claims data (2006–2015), we conducted a retrospective cohort study of nonpregnant women 18–44 years who received an outpatient diagnosis of UTI with a prescription for an antibiotic with activity against common uropathogens. For each antibiotic agent, we estimated the daily cumulative risk and 95% confidence intervals (CIs) of treatment failure defined by a subsequent UTI-related antibiotic prescription since the index prescription. Propensity-score weighting accounted for patient-, geographic-, and provider-level characteristics. Results: Among 1, 100, 661 eligible women, the majority received second-line fluoroquinolones (43%), first-line trimethoprim-sulfamethoxazole (28%), or first-line nitrofurantoin (24%). Seven-day and 30-day treatment failure occurred in 8.4% ( n = 92, 382) and 20.5% ( n = 225, 746) of women, respectively. Among initiators of first-line agents, the 7-day weighted cumulative incidence estimates of treatment failure were lower for nitrofurantoin (6.0%, 95% CI, 5.9%–6.1%) vs. trimethoprim-sulfamethoxazole (8.8%, 95% CI, 8.7%–9.0%). Among initiators of second-line agents, treatment failure did not differ between fluoroquinolones (5.0%, 95% CI, 4.9%–5.1%), narrow-spectrum β-lactams (5.1%, 95% CI, 4.9%–5.4%), or broad-spectrum β-lactams (5.3%, 95% CI, 4.9%–5.7%). Among initiators of nonguideline recommended β-lactams, treatment failure was 9.6% (95% CI, 9.0%–10.3%). Results were similar for 30-day treatment failure, with the exception of lower risk for fluoroquinolones compared with other second-line agents. Conclusion: The risk of treatment failure differs widely by antibiotic agent, with substantial differences between two first-line agents. Understanding the effectiveness of antibiotic therapy is critical to guide clinical decision making, reduce suboptimal antibiotic prescribing, and prevent antibiotic resistance and other adverse events. Disclosures: All authors: No reported disclosures.